3D-imaging of human skin - optical in vivo tomography and topology by short coherence interferometry - Häusler, Gerd; et al. (Proceedings of SPIE, 1997)
We discuss different modifications of white light interferometry, for the acquisition of human skin morphology. In a first experiment we display the diffusion of light within tissue, versus time. Light is focused onto the surface of the sample, penetrates the sample, is scattered and partly emerges from the surface again. For each point of the surface we can measure a certain run time profile of the emerging photons, via the speckle contrast. The local scattering behavior of the skin is encoded in the run time profile. Further we present a sensor for the acquisition of cross-sectional images of volume scatterers, we call it "spectral radar." The scattering amplitude a(z) along one vertical axis from the surface into the bulk can be measured within one exposure. No reference arm scanning is necessary, hence a short measurement time is possible. The depth uncertainty within a range of 1000 μm is about 10 μm. In first measurements we distinguished a melanoma maligna from healthy skin, in vitro and we measured the thickness of a fingernail in vivo. We further demonstrate a third method, the "coherence radar" for in vivo measurements of skin surface topology, with an accuracy of a few micrometers, and a field of 512 x 512 pixels. ©2004 Copyright SPIE - The International Society for Optical Engineering.
UnivIS-Import:2015-03-05:Pub.1997.nat.dphy.optik.1optik.3dimag
Keywords: Coherence radar; Human skin; Multiple scattering; Oct; Short coherence interferometry; Skin cancer; Spectral radar; Texture analysis; Volume scatterer

3D Real Time Camera - Häusler, Gerd; et al. (Proc. of the 3rd Int. Workshop on Automatic Processing of Fringe Patterns, 1997)
UnivIS-Import:2015-04-16:Pub.1997.nat.dphy.optik.1optik.3dreal

About the scaling behavior of optical range sensors - Häusler, Gerd (Proc. of the 3rd Int. Workshop on Automatic Processing of Fringe Patterns, 1997)
UnivIS-Import:2015-04-16:Pub.1997.nat.dphy.optik.1optik.aboutt

A Fibre-Optical Implementation of Range Sensors, based on the 'Spectral Radar' - Häusler, Gerd; et al. (Proceedings of the EOS Topical Meeting Free Space Micro-Optical Systems, 1996)
UnivIS-Import:2015-04-16:Pub.1996.nat.dphy.optik.1optik.afibre

Akquisition und Verarbeitung von 3D-Daten für die angewandte Messtechnik - Häusler, Gerd; et al. (Bildverarbeitung '97: Forschen, Entwickeln, Anwenden, 1997)
UnivIS-Import:2015-04-16:Pub.1997.nat.dphy.optik.1optik.akquis

A new approach for modeling and smoothing of scattered 3D data - Häusler, Gerd; et al. (Proceedings of SPIE, 1998)
In order to digitize the whole surface of a three-dimensional object by means of an optical range sensor, usually multiple range images are acquired from different viewpoints and merged into a single surface description. The simplest and most accurate way is to generate a polyhedral surface. The data are usually distorted by measuring errors like noise, aliasing, outliers, calibration and registration errors, etc., so that they have to be filtered. Calibration and registration errors first appear after merging of different views. As the merged data are no longer represented on a grid, conventional filters for digital signal processing are not applicable. We introduce a new approach for modeling and smoothing scattered data based on an approximation of a mesh of circular arcs. This new method enables interpolation of curved surfaces using solely the vertex position and the associated vertex normals of a polyhedral mesh. The new smoothing filter is specifically adapted to the requirements of geometric data, as it minimizes curvature variations. In contrast to linear filters, undesired surface undulations are avoided, which is an important pre-condition for NC milling and rendering.
UnivIS-Import:2015-03-05:Pub.1998.nat.dphy.optik.1optik.anewap
Keywords: Geometric modeling; Reverse engineering; Scattered data interpolation; Scattered data modeling; Smoothing of polyhedral surfaces; Surface approximation; Surface interpolation; Surface reconstruction; Surface smoothing

A new method of short-coherence interferometry in human skin (in vivo) and in solid volume scatterers - Häusler, Gerd; et al. (SPIE j, 1996)
UnivIS-Import:2015-03-05:Pub.1996.nat.dphy.optik.1optik.anewme

A Non-linear Subdivision Scheme for Triangle Meshes - Häusler, Gerd; et al. (Proc. of Vision, Modeling and Visualization 2000, 2000)
UnivIS-Import:2015-04-16:Pub.2000.nat.dphy.optik.1optik.anonli

A Robust Multiresolution Registration Approach - Häusler, Gerd; et al. (Proc. of Vision, Modeling and Visualization '99, 1999)
UnivIS-Import:2015-04-16:Pub.1999.nat.dphy.optik.1optik.arobus

A Sub-Atomic Subdivision Approach - Häusler, Gerd; et al. (Proc. of Vision, Modeling and Visulaisation, 2001)
UnivIS-Import:2015-04-16:Pub.2001.nat.dphy.optik.1optik.asubat

Aufbereitung von 3D-Sensordaten für Reverse Engineering mit Slim3D - Häusler, Gerd; et al. (Optische 3D-Formerfassung, 1998)
UnivIS-Import:2015-04-16:Pub.1998.nat.dphy.optik.1optik.aufber

Automatic Coarse Registration of 3D Surface Data in Oral and Maxillofacial Surgery - Nkenke, Emeka; Neukam, Friedrich Wilhelm; Häusler, Gerd; et al. (Perspective in Image-Guided Surgery, Proceedings of the Scientific Workshop on Medical Robotics, Navigation and Visualizatiom, 2004)
UnivIS-Import:2015-04-16:Pub.2004.nat.dphy.optik.1optik.autima

Automatic registration method for multisensor datasets adopted for dimensional measurements on cutting tools - Shaw, Laura; Ettl, Svenja; Mehari, Fanuel; Weckenmann, Albert; Häusler, Gerd (Measurement Science & Technology, 2013)
Multisensor systems with optical 3D sensors are frequently employed to capture complete surface information by measuring workpieces from different views. During coarse and fine registration the resulting datasets are afterward transformed into one common coordinate system. Automatic fine registration methods are well established in dimensional metrology, whereas there is a deficit in automatic coarse registration methods. The advantage of a fully automatic registration procedure is twofold: it enables a fast and contact-free alignment and further a flexible application to datasets of any kind of optical 3D sensor. In this paper, an algorithm adapted for a robust automatic coarse registration is presented. The method was originally developed for the field of object reconstruction or localization. It is based on a segmentation of planes in the datasets to calculate the transformation parameters. The rotation is defined by the normals of three corresponding segmented planes of two overlapping datasets, while the translation is calculated via the intersection point of the segmented planes. First results have shown that the translation is strongly shape dependent: 3D data of objects with non-orthogonal planar flanks cannot be registered with the current method. In the novel supplement for the algorithm, the translation is additionally calculated via the distance between centroids of corresponding segmented planes, which results in more than one option for the transformation. A newly introduced measure considering the distance between the datasets after coarse registration evaluates the best possible transformation. Results of the robust automatic registration method are presented on the example of datasets taken from a cutting tool with a fringe-projection system and a focus-variation system. The successful application in dimensional metrology is proven with evaluations of shape parameters based on the registered datasets of a calibrated workpiece. © 2013 IOP Publishing Ltd.
UnivIS-Import:2015-04-14:Pub.2013.tech.FT.FT-QMFMT.automa
Keywords: automatic registration; cutting tools; three-dimensional metrology

Automatische Porenfindung in 3D-CT Daten - Häusler, Gerd; et al. (2001)
UnivIS-Import:2015-04-14:Pub.2001.forsch.gradui.gradui_6.automa

Automatische Segmentierung der Gewebegrenzen in 2D-Ultraschalldaten aus der Mund-Kiefer- und Gesichtschirurgie - Häusler, Gerd; Wittenberg, Thomas; Nkenke, Emeka; Ettl, Svenja; et al. (Informatik aktuell, 2006)
UnivIS-Import:2015-03-09:Pub.2006.nat.dphy.optik.1optik.automa

Broadband Operation of a Gain Switched TI:Sapphire Laser for Coherence Radar Measurements - Häusler, Gerd; et al. (Proceedings of SPIE, 1999)
UnivIS-Import:2015-03-05:Pub.1999.nat.dphy.optik.1optik.broadb

Coherence Radar and Spectral Radar - New Tools for Dermatological Diagnosis - Häusler, Gerd; et al. (Journal of Biomedical Optics, 1998)
"Coherence radar," an optical 3-D sensor based on short coherence interferometry, is used to measure skin surface topology. This method is called optical coherence profilometry (OCP) and it may be a useful tool for medical diagnosis in dermatology because different medical conditions show distinct alterations of the skin surface. The measuring uncertainty is less than 2 μm. The measuring time is about 4 s. in vivo 3-D mapping of naked skin was performed without preparation. For clinical application, a fiber optical implementation was introduced. Spectral radar is an optical sensor for the acquisition of skin morphology based on OCT techniques. The scattering amplitude a(z) along one vertical axis from the surface into the bulk can be measured within one exposure. No reference arm scanning is necessary. The theory of the sensor, including the dynamic range, is discussed and in vivo measurements of human skin by a fiber optical implementation of the sensor are demonstrated. © 1998 Society of Photo-Optical Instrumentation Engineer
UnivIS-Import:2015-03-05:Pub.1998.nat.dphy.optik.1optik.cohere
Keywords: Coherence radar; Fourier spectroscopy; Human skin; In vivo measurements; Melanoma maligna; Optical coherence profilometry; Optical coherence tomography; Speckle interferometry; Spectral radar; Volume scatterers

'Coherence Radar' - New Modifications of White Light Interferometry for Large Objects Shape Acquisition - Häusler, Gerd; et al. (Proc. of the EOS Topical Meeting on Optoelectronics Distance Measurements and Applications, 1997)
UnivIS-Import:2015-04-16:Pub.1997.nat.dphy.optik.1optik.cohere

"Coherence Radar, Spectral Radar, Dispersion Radar": Modifications of Broad Band Interferometry for High Accuracy 3D-Measurements in Medicine and Industry - Häusler, Gerd; et al. (Proc. of ODIMAP II, 1999)
UnivIS-Import:2015-04-16:Pub.1999.nat.dphy.optik.1optik.cohere

Corrupting coherence - ubquitous inthe metrologists daily life - Häusler, Gerd (Proc. of 3rd Topical Meeting onOptoelectronic Distance Measurement and Applications (ODIMAP III), 2001)
UnivIS-Import:2015-04-16:Pub.2001.nat.dphy.optik.1optik.corrup

Deflectometric measurement of large mirrors - Olesch, Evelyn; Häusler, Gerd; Wörnlein, André; Stinzing, Friedrich; van Eldik, Christopher (Advanced Optical Technologies, 2014)
We discuss the inspection of large-sized, spherical mirror tiles by 'Phase Measuring Deflectometry' (PMD). About 10 000 of such mirror tiles, each satisfying strict requirements regarding the spatial extent of the point-spreadfunction (PSF), are planned to be installed on the Cherenkov Telescope Array (CTA), a future ground-based instrument to observe the sky in very high energy gamma-rays. Owing to their large radii of curvature of up to 60 m, a direct PSF measurement of these mirrors with concentric geometry requires large space. We present a PMD sensor with a footprint of only 5 ?2 ?1.2 m3 that overcomes this limitation. The sensor intrinsically acquires the surface slope; the shape data are calculated by integration. In this way, the PSF can be calculated for real case scenarios, e.g., when the light source is close to infinity and off-axis. The major challenge is the calibration of the PMD sensor, specifically because the PSF data have to be reconstructed from different camera views. The calibration of the setup is described, and measurements presented and compared to results obtained with the direct approach.
Keywords: 3D-metrology; Deflectometry; Interferometry; Optical testing; Telescope

Digitizing 3D objects for Reverse Engineering and Virtual Reality - Häusler, Gerd; et al. (Principles of 3D Image Analysis andSynthesis, 2000)
UnivIS-Import:2015-04-20:Pub.2000.nat.dphy.optik.1optik.digiti

Discover better optical sensors - By exploring and exploiting nature's limits - Häusler, Gerd (Optics InfoBase Conference Papers, 2019)
Nature's limits are precious: they often reveal uncertainty products connecting coherence, resolution, precision, channel capacity… So we can bargain with nature for "optimal" 3D sensors with novel features or just better precision, resolution, speed.
CRIS-Team Scopus Importer:2021-04-20

Eine neue Methode zur Abformung sensibler Objekte - Häusler, Gerd; et al. (Restauro, 2001)
UnivIS-Import:2015-03-09:Pub.2001.nat.dphy.optik.1optik.einene

Fast 3d - Camera for Industrial and Medical Applications - Häusler, Gerd; et al. (Proc. of ODIMAP II, 1999)
UnivIS-Import:2015-04-16:Pub.1999.nat.dphy.optik.1optik.fast3d

Flying triangulation - A motion-robust optical 3D sensor for the real-time shape acquisition of complex objects - Häusler, Gerd; Ettl, Svenja; Arold, Oliver; Yang, Zheng (Applied Optics, 2012)
Three-dimensional (3D) shape acquisition is difficult if an all-around measurement of an object is desired or if a relative motion between object and sensor is unavoidable. An optical sensor principle is presented-we call it "flying triangulation"-that enables a motion-robust acquisition of 3D surface topography. It combines a simple handheld sensor with sophisticated registration algorithms. An easy acquisition of complex objects is possible-just by freely hand-guiding the sensor around the object. Real-time feedback of the sequential measurement results enables a comfortable handling for the user. No tracking is necessary. In contrast to most other eligible sensors, the presented sensor generates 3D data from each single camera image.
Keywords: optical 3D metrology; motion robust; triangulation

Fortschritte bei der Automatisierung des Reverse Engineering - Häusler, Gerd; et al. (Optische Formerfassung, 1997)
UnivIS-Import:2015-04-16:Pub.1997.nat.dphy.optik.1optik.fortsc

Fusion of computed tomography data and optical 3D images of the dentition for streak artefact correction in the simulation of orthognathic surgery - Nkenke, Emeka; Häusler, Gerd; Lell, Michael; et al. (Dentomaxillofacial Radiology, 2004)
Objective: To determine the limits of accuracy of fusion of optical three-dimensional (3D) imaging and computed tomography (CT) with and without metal artefacts in an experimental setting and to show the application of this hybrid system in 3D orthognathic surgery simulation. Methods: Ten plaster casts of dental arches were subjected to a CT scan and optical 3D surface imaging. Subsequently, the first molars in the plaster casts were supplied with metal restorations, bilaterally, and new CT scans and optical surface images were assessed. The registration of the surface data of the two imaging modalities of the study models without and with metal restorations was carried out. The mean distance between the two data sets was calculated. From a patient a CT scan of the skull as well as optical 3D images of plaster casts of the dental arches were acquired. Again the two imaging modalities were registered and virtual orthognathic surgery simulation was carried out. Results: The mean distance between the corresponding data points of CT and optical 3D surface images was 0.1262 ±0.0301 mm and 0.2671±0.0580 mm, respectively, for the plaster casts without and with metal restorations. The differences between these data were statistically significant (P< 0.0005). For the patient case a mean difference of 0.66±0.49 mm and 0.56±0.48 mm for mandible and maxilla, respectively, was calculated between CT and optical surface data. Conclusion: The accuracy of the fusion of 3D CT surface data and optical 3D imaging is significantly reduced by metal artefacts. However, it seems appropriate for virtual orthognathic surgery simulation, as post-operative orthodontics are performed frequently. © 2004 The British Institute of Radiology.
UnivIS-Import:2015-04-14:Pub.2004.nat.dphy.optik.1optik.fusion
Keywords: Computed tomography; Image fusion; Metal artefacts; Optical 3D imaging; Phase measuring triangulation

Hertel exophtalmometry versus computed tomography and optical 3D imaging for the determination of the globe position in zygomatic fractures - Häusler, Gerd; Nkenke, Emeka; Neukam, Friedrich Wilhelm; et al. (International Journal of Oral and Maxillofacial Surgery, 2004)
UnivIS-Import:2015-03-09:Pub.2004.nat.dphy.optik.1optik.hertel

Highly improved range sensing - by reduction of spatial coherence - Häusler, Gerd; et al. (Optik, 2001)
Optical range sensors based on triangulation are widely used for the shape measurement of optically rough objects. The origin of the achievable measuring uncertainty of the distance is speckle noise. Speckle noise is unavoidable in spatially coherent systems. We demonstrate two experiments which prove that without spatial coherence, the measuring uncertainty can be dramatically reduced, and we present an on-line 3D-sensor for laser-material processing, exploiting this knowledge.
UnivIS-Import:2015-03-09:Pub.2001.nat.dphy.optik.1optik.highly
Keywords: Coherent noise; Distance measurement; Laser material processing; Optical metrology; Triangulation

Holographic Measurement of Surface Topography - Limits and New Options - Häusler, Gerd; Willomitzer, Florian (DGsO-Proceedings 2023, 2023)
There is a plethora of options for optical 3D-metrology. Inspired by the progress of digital holography, we discuss two questions: Can we implement all classical (non-holographic) sensors via digital holography? And even more interesting: Can digital holography enable options beyond classical sensors?
Keywords: holography; metrology; topography; 3-D

How much 3D-Information can weacquire? Optical Range Sensors at the Physical Limit, and where to apply them - Häusler, Gerd (Proceedings of Third International Conference on 3-DDigital Imaging and Modeling, 2001)
UnivIS-Import:2015-04-16:Pub.2001.nat.dphy.optik.1optik.howmuc

How much should we pay for optical 3d-sensors? - a respectable scientific question - Häusler, Gerd (Proceedings of ICO 04, Tokyo, 2004)
UnivIS-Import:2015-03-09:Pub.2004.nat.dphy.optik.1optik.howmuc

Imaging: Speckle and Coherence - Häusler, Gerd (Encyclopedia of Modern Optics, 2004)
UnivIS-Import:2015-04-20:Pub.2004.nat.dphy.optik.1optik.imagin

Improved white-light interferometry on rough surfaces by statistically independent speckle patterns - Häusler, Gerd; Hybl, Ondrej; Wiesner, Bernhard (Applied Optics, 2012)
White-light interferometry (WLI) on rough surfaces is based on interference from individual speckles. The measurement uncertainty of WLI is limited by a random shift of these individual interference patterns. The statistical error in each measurement point depends on the brightness of the corresponding speckle: a dark speckle yields a larger error than a bright speckle. In this paper, a novel method is presented to reduce the measurement uncertainty significantly: by sequentially switching the direction of the illumination, the camera sees several independent speckle patterns in sequence. From each pattern, the brightest speckles are selected to eventually calculate an accurate height map. This height map displays no outliers, and the measured surface roughness is close to the stylus measurements.

Information theoretical optimization for optical range sensors, - Häusler, Gerd; et al. (Applied Optics, 2003)
Most of the known optical range sensors require a large amount of two-dimensional raw data from which the three-dimensional (3D) data are decoded and so are associated with considerable cost. The cost arises from expensive hardware as well as from the time necessary to acquire the images. We will address the question of how one can acquire maximum shape information with a minimum amount of image raw data, in terms of information theory. It is shown that one can greatly reduce the amount of raw data needed by proper optical redundancy reduction. Through these considerations, a 3D sensor is introduced, which needs only a single color (red-green-blue) raw image and still delivers data with only approximately 2-μm longitudinal measurement uncertainty. © 003 Optical Society of America.
UnivIS-Import:2015-03-09:Pub.2003.nat.dphy.optik.1optik.inform

In Process 3D-Sensing for Laser Material Processing - Häusler, Gerd; et al. (Proc. of Third International Conference on 3D Digital Imaging and Modeling, 2001)
UnivIS-Import:2015-04-16:Pub.2001.forsch.gradui.gradui_6.inproc

Instantaneous speckle reduction? Yes, but there is no free lunch! - Häusler, Gerd; Dötzer, Florian; Mantel, Klaus (Proceedings of SPIE - The International Society for Optical Engineering, 2018)
We are motivated by the question if scanning laser projection with low speckle noise is possible. Scanning laser projection requires "instantaneous" speckle reduction, within a few nanoseconds-meaning that no moving diffusors can be used. We will argue that instantaneous speckle reduction is possible by conversion of spatial coherence to spatial incoherence-but nature demands for a compensation. The cost can be estimated via the information theoretical concept "channel capacity", which incorporates the etendue as well as the signal-to-noise ratio. We will show that an optical system with low spatial coherence (=low speckle noise) must provide significantly more degrees of freedom than a coherent imaging system. The consequence for the technical optical system is serious: Significant speckle reduction can only be achieved by an excessively large projection aperture. This is not just a sophistic consideration, it seriously restricts the design of scanning laser projectors.
Created from Fastlane, Scopus look-up
Keywords: Channel capacity; Etendue; Laser projection; Speckle noise; Speckle noise reduction

Ist 'Technisches Sehen' gleich 'Kamera + Computer'? - Häusler, Gerd; Leuchs, Gerd (Uni-Kurier-Magazin, 2003)
UnivIS-Import:2015-03-09:Pub.2003.nat.dphy.optik.1optik.isttec

Kalibrierung einer 3D Video Kamera - Häusler, Gerd; et al. (3.Optische Formerfassung, 1996)
UnivIS-Import:2015-04-16:Pub.1996.nat.dphy.optik.1optik.kalibr

Kalibrierung von optischen 3D-Sensoren - Häusler, Gerd; et al. (Optik, 1996)
UnivIS-Import:2015-03-05:Pub.1996.nat.dphy.optik.1optik.kalibr_2

Kohärenzradar - ein 3D-Sensor im Genauigkeitsbereich von 1 µ - Häusler, Gerd; et al. (Technisches Messen, 2000)
UnivIS-Import:2015-03-09:Pub.2000.nat.dphy.optik.1optik.kohren

Large field-of-view scanning white-light interferometers - Häusler, Gerd; et al. (18th Annual Meeting of American Society for Precision Engineering, 2003)
UnivIS-Import:2015-03-09:Pub.2003.nat.dphy.optik.1optik.largef

Laser triangulation: Fundamental uncertainty in distance measurement - Häusler, Gerd; et al. (Applied Optics, 1994)
This paper presents a theoretical discussion of the fundamental uncertainty of distance measurements by caused by speckle during laser triangulation. Other contributing factors are the observation aperture and the angle of triangulation. For short-range macroscopic applications this uncertainty is in the range of couple micrometers to more than 10 μm, and is independent of the size of the spot size projected, provided this spot is larger than the observed speckle. Low temporal illumination reduces the uncertainty by more than twice for rough surfaces, although N-fold loss of lateral resolution results from an N-fold improvement in the distance uncertainty.
UnivIS-Import:2015-03-05:Pub.1994.nat.dphy.optik.1optik.lasert

Limits of Optical Range Sensors and How to Exploit Them - Häusler, Gerd; et al. (Trends in Optics and Phototonics, 1999)
UnivIS-Import:2015-04-20:Pub.1999.nat.dphy.optik.1optik.limits

Localization and registration of 3D-objects in space - where are the limits? - Häusler, Gerd; et al. (Applied Optics, 2001)
UnivIS-Import:2015-03-09:Pub.2001.nat.dphy.optik.1optik.locali

Management of spontaneous enophthalmos due to silent sinus syndrome: a case report - Nkenke, Emeka; Alexiou, Christoph; Iro, Heinrich; Amann, Kerstin Ute; Kirchner, Thomas; Häusler, Gerd; Neukam, Friedrich Wilhelm; Holbach, Benedict (International Journal of Oral and Maxillofacial Surgery, 2005)
UnivIS-Import:2015-04-14:Pub.2005.nat.dphy.optik.1optik.manage

Methods for Optical Shape Measurement and their Measurement Uncertainty - Pavliček, Pavel; Häusler, Gerd (International Journal of Optomechatronics, 2014)
There is a wide spectrum of optical 3-D sensors based on only a few basic principles. We calculate the measurement uncertainty for several “paradigm” methods, by means of the Cramér-Rao lower bound. It turns out that when all other sources of noise are neglected, the shot noise becomes the ultimate limit of the measurement uncertainty and the measurement uncertainty can be traced back to a Heisenberg uncertainty product. Consequently, making one of the factors uncertain, the other factor will become more precise. The different methods vary only by the way how this “uncertainty” is generated.
Created from Fastlane, Scopus look-up
Keywords: coherence noise; measurement uncertainty; shape measurement; shot noise; uncertainty relation

Metrical calibration of a Phase measuring triangulation sensors - Häusler, Gerd; et al. (Proceedings of the Vision Modeling and Visualization Conference 2001, 2000)
UnivIS-Import:2015-03-09:Pub.2000.nat.dphy.optik.1optik.metric

Microdeflectometry - a novel tool to acquire three-dimensional microtopography with nanometer height resolution - Häusler, Gerd; Richter, Claus; Leitz, Karl-Heinz; Knauer, Markus C. (Optics Letters, 2008)
We introduce "microdeflectometry," a novel technique for measuring the microtopography of specular surfaces. The primary data are the local slope of the surface under test. Measuring the slope instead of the height implies high information efficiency and extreme sensitivity to local shape irregularities. The lateral resolution can be better than 1 μm, whereas the resulting height resolution is in the range of 1 nm. Microdeflectometry can be supplemented by methods to expand the depth of field, with the potential to provide quantitative 3D imaging with scanning-electron-microscope-like features. © 2008 Optical Society of America.
LFT Import::2019-07-29 (1515)

Modifications of the coherence radar for in vivo profilometry in dermatology - Häusler, Gerd; et al. (SPIE j, 1998)
UnivIS-Import:2015-03-05:Pub.1998.nat.dphy.optik.1optik.modifi

Möglichkeiten und Grenzen optischer 3D-Sensoren in der industriellen Praxis - Häusler, Gerd (Optische Messtechnik an diffus reflektierenden Medien, 1997)
UnivIS-Import:2015-04-20:Pub.1997.nat.dphy.optik.1optik.mglich

Neue Ergebnisse in der optischen Datengewinnung und der Weiterverarbeitung - Häusler, Gerd; et al. (Optische 3D-Formerfassung, 1999)
UnivIS-Import:2015-04-16:Pub.1999.nat.dphy.optik.1optik.neueer

New Modifications of the Coherence Radar - Häusler, Gerd; et al. (Proc. of the 3rd Int. Workshop on Automatic Processing of Fringe Patterns, 1997)
UnivIS-Import:2015-04-16:Pub.1997.nat.dphy.optik.1optik.newmod

New Range Sensors at the Physical Limit of Measuring Uncertainty - Häusler, Gerd; et al. (Proc. of the EOS Topical Meeting on Optoelectronics Distance Measurements and Applications, 1997)
UnivIS-Import:2015-04-16:Pub.1997.nat.dphy.optik.1optik.newran

Observation of light propagation in volume scatterers with 10 11-fold slow motion - Häusler, Gerd; et al. (Optics Letters, 1996)
UnivIS-Import:2015-03-05:Pub.1996.nat.dphy.optik.1optik.observ

Optical 3D Sensors - Häusler, Gerd (Principles of 3D Image Analysis and Synthesis, 2000)
UnivIS-Import:2015-04-20:Pub.2000.nat.dphy.optik.1optik.optica_0

Optical Coherence Profilometry (OCP) of human skin in vivo - Häusler, Gerd; et al. (SPIE j, 1997)
UnivIS-Import:2015-03-05:Pub.1997.nat.dphy.optik.1optik.multic

Optical Coherence Tomography by 'spectral radar': dynamic range estimation and in vivo measurements of skin - Häusler, Gerd; et al. (Proceedings of SPIE, 1998)
UnivIS-Import:2015-03-05:Pub.1998.nat.dphy.optik.1optik.optica

Optical Coherence Tomography by "Spectral Radar": Improvement of Signal-to-Noise Ratio - Häusler, Gerd; et al. (Proceedings of SPIE, 2000)
`Spectral radar' combines a white light interferometer with a spectrometer. It is an optical sensor for the acquisition of skin morphology based on OCT techniques. The scattering amplitude along one vertical axis from the surface into the bulk can be measured within one exposure. We will discuss some essentials of signal formation and a new method of signal evaluation that significantly reduces artifacts from some source imperfections. We will further demonstrate new measurements.
UnivIS-Import:2015-03-09:Pub.2000.nat.dphy.optik.1optik.optica_4

Optical coherence tomography with the Spectral Radar. Fast optical analysis in volume scatterers by short coherence interferometry - Häusler, Gerd; et al. (SPIE j, 1996)
We present a sensor for acquisition of cross-sectional images of volume scatterers, we call it 'spectral radar'. Medical and technical applications are possible. The sensor is a modified Michelson interferometer, with a broad bandwidth light source. The scattering amplitude a(z) along one vertical axis from the surface into the bulk can be measured within one exposure. No reference arm scanning is necessary. Measurement results of stationary and non stationary scattering phantoms, human skin and of a fish eye in vitro are show
UnivIS-Import:2015-03-05:Pub.1996.nat.dphy.optik.1optik.optica_3

Optical Range Sensing with spatially modulated Coherence - Häusler, Gerd; et al. (Proc. of the Int. Symp. on Laser Applications in Precision Measurements, 1996)
UnivIS-Import:2015-04-16:Pub.1996.nat.dphy.optik.1optik.optica

Optical Tomography: 3D-Metrology in Scattering Media - Häusler, Gerd; et al. (3D-Image Analysis and Synthesis, 1996)
UnivIS-Import:2015-04-20:Pub.1996.nat.dphy.optik.1optik.optica_1

Optimization of white light interferometry at rough surfaces by error analysis - Häusler, Gerd; et al. (Optik, 2004)
White light interferometry can be used to measure the shape of rough surfaces. At rough surfaces, the measuring uncertainty in principle cannot be better than the surface roughness, which is commonly in the range of 1 micron. Hence, the requirements for the hard- and software components of the instrument are not as high as for interferometry in the nanometer regime. An analysis of the dominant error sources allows the design of an "optimal" sensor with a measuring uncertainty as small as physically possible, with components as good as necessary and as simple as possible.
UnivIS-Import:2015-03-09:Pub.2004.nat.dphy.optik.1optik.optimi
Keywords: Measuring uncertainty; White light interferometry

Optische 3D-Messtechnik in der Mund-, Kiefer-, Gesichtschirurgie - Häusler, Gerd; Nkenke, Emeka; et al. (Informatik 2005 - Informatik live! (35. Jahrestagung der Ges. für Informatik e.V.), 2005)
UnivIS-Import:2015-04-20:Pub.2005.nat.dphy.optik.1optik.optisc

Optische 3D-Sensoren helfen dem Restaurator - Häusler, Gerd; et al. (Das moderne Museum - Die Vorträge der MUTEC 99, 2001)
UnivIS-Import:2015-04-16:Pub.2001.nat.dphy.optik.1optik.optisc

Optische 3D-Sensoren mit großem Meßbereich und hoher Genauigkeit - Häusler, Gerd; et al. (Info Phys Tech, 1995)
UnivIS-Import:2015-03-05:Pub.1995.nat.dphy.optik.1optik.optisc_7

Optische 3D-Sensoren und deren industrielle Anwendung - Häusler, Gerd; et al. (Technisches Messen, 1996)
UnivIS-Import:2015-03-05:Pub.1996.nat.dphy.optik.1optik.ptisch

Optische Messtechnik an diffus reflektierenden Medien - Häusler, Gerd; et al. (Expert-Verlag, 1997)
UnivIS-Import:2015-05-08:Pub.1997.nat.dphy.optik.1optik.mglich

Optischer Sensor wacht über Lasermaterialbearbeitung - Häusler, Gerd; et al. (F and M; Feinwerktechnik, Mikrotechnik, Messtechnik, 1995)
UnivIS-Import:2015-03-05:Pub.1995.nat.dphy.optik.1optik.optisc

Phase Measuring Deflectometry: a new approuch to measure specular free-form surfaces - Häusler, Gerd; et al. (Proceedings of SPIE, 2004)
UnivIS-Import:2015-03-09:Pub.2004.nat.dphy.optik.1optik.phasem

Physikalische Grenzen der Formerfassung mit Licht - Häusler, Gerd; Leuchs, Gerd (Physikalische Blätter, 1997)
UnivIS-Import:2015-03-05:Pub.1997.nat.dphy.optik.1optik.physik

Processing Range Data for Reverse Engineering and Virtual Reality - Häusler, Gerd; et al. (Proceedings of Third International Conference on 3-DDigital Imaging and Modeling, 2001)
UnivIS-Import:2015-04-16:Pub.2001.nat.dphy.optik.1optik.proces

Range Sensing of the first, the second, and the third kind - Häusler, Gerd (Proc. of the EOS Topical Meetings Digest Series, 1994)
UnivIS-Import:2015-04-16:Pub.1994.nat.dphy.optik.1optik.ranges

Reconstruction of smoothed polyhedral surfaces from multiple range images - Häusler, Gerd; et al. (3D Image Analysis and Synthesis '97, 1997)
UnivIS-Import:2015-04-20:Pub.1997.nat.dphy.optik.1optik.recons

Refining Triangle Meshes by Non-Linear Subdivision - Häusler, Gerd; et al. (Proceedings of Third International Conference on 3-DDigital Imaging and Modeling, 2001)
UnivIS-Import:2015-04-16:Pub.2001.nat.dphy.optik.1optik.refini

Reflections about the holographic and non-holographic acquisition of surface topography: where are the limits? - Häusler, Gerd; Willomitzer, Florian (Light: Advanced Manufacturing, 2022)
Recording and (computational) processing of complex wave fields offer a vast realm of new methods for optical 3D metrology. We discuss fundamental similarities and differences between holographic surface topography measurement and non-holographic principles, such as triangulation, classical interferometry, rough surface interferometry and slope measuring methods. Key features are the physical origin of the ultimate uncertainty limit and how the topographic information is encoded and decoded. Besides the theoretical insight, the discussion will help optical metrologists to determine if their measurement results could be improved or have already hit the ultimate limit of what physics allows.
Created from Fastlane, Scopus look-up
Keywords: Holography; Optical metrology; Physical limits; Topography

Reverse Engineering mit Hilfe optischer 3D-Sensoren - Häusler, Gerd; et al. (Optische 3D-Erfassung großer Objekte, 1996)
UnivIS-Import:2015-04-16:Pub.1996.nat.dphy.optik.1optik.revers

Reverse engineering using optical 3D sensors - Häusler, Gerd; et al. (Proceedings of SPIE, 1998)
Optical 3D sensors are used as tools for reverse engineering: First the shape of an object is digitized by acquisition of multiple range images from different view points. Then the range images are registered and the data is turned into a CAD description, e.g. tensor product surfaces, by surface modeling software. For many applications however it is sufficient to generate a polyhedral surface. We present a nearly automatic procedure covering the complete task of data acquisition, calibration, surface registration and surface reconstruction using a mesh of triangles. A couple of measurements, such as teeth, works of art and cutting tools are shown.
UnivIS-Import:2015-03-05:Pub.1998.nat.dphy.optik.1optik.revers
Keywords: 3D sensing; Calibration; Optical 3D sensor; Registration; Reverse engineering; Surface reconstruction; Triangulation

Reverse Engineering using Optical Range Sensors - Häusler, Gerd; et al. (Handbook of Computer Vision and Applications Vol. 3: Systems and Applications, 1999)
UnivIS-Import:2015-04-20:Pub.1999.nat.dphy.optik.1optik.revers

Sparse Active Triangulation Grids for Respiratory Motion Management - Bauer, Sebastian; Ettl, Svenja; Wasza, Jakob; Willomitzer, Florian; Huber, Franz; Hornegger, Joachim; Häusler, Gerd (DGaO Proceedings 2012, 2012)

Spectral Radar: OCT in the Fourier Domain - Häusler, Gerd; et al. (Handbook of Optical Coherence Tomography, 2001)
UnivIS-Import:2015-04-20:Pub.2001.nat.dphy.optik.1optik.spectr

The effect of the high surface roughness in a comparative process - Häusler, Gerd; et al. (Optics and Lasers in Engineering, 2002)
Comparative measurement methods are used to compare the behaviour of two macroscopically identical but microscopically different object surfaces. The roughness of these surfaces can have any value. The aim of this paper is to demonstrate theoretically as well as experimentally, the effect and the limitations of the high surface roughness on the visibility of the difference correlation fringes obtained in comparative processes. © 2001 Elsevier Science Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2002.nat.dphy.optik.1optik.theeff
Keywords: Comparative holography; Difference correlation fringes; Surface roughness; Visibility

Three-Dimensional Sensors - Potentials and Limitations - Häusler, Gerd (Handbook of Computer Vision and Applications, Vol. 1: Sensors and Imaging, 1999)
UnivIS-Import:2015-04-20:Pub.1999.nat.dphy.optik.1optik.threed

Über die kluge Auswahl und Anwendung optischer 3D-Sensoren - Häusler, Gerd; et al. (Photonik, 2004)
UnivIS-Import:2015-03-09:Pub.2004.nat.dphy.optik.1optik.berdie

Ubiquitous coherence - boon and bale of the optical metrologist - Häusler, Gerd (Proceedings of SPIE, 2003)
Commonly, optical systems are called coherent, if a laser is used (right), and incoherent if other sources come into play (wrong). Most opticists are not aware that parasitic spatial coherence is ubiquitous, even if it is unobvious. The pretended incoherent approach may lead to significant quantitative measuring errors of illumination or reflectivity, 3d shape, size or distance. On the other hand, a favourable property of spatial coherence is that among the "speckle noise" we may reveal useful information about the object, by white light interferometry. This report will discuss simple rules to estimate the occuring errors and how to reduce spatial coherence. We will further discuss the complex signal formation in white light interferometry and roughness measurements far beyond the bandwidth limit of the observing optics.
UnivIS-Import:2015-03-09:Pub.2003.nat.dphy.optik.1optik.ubiqui
Keywords: Coherence; Coherence radar; Measuring uncertainty; Roughness measurement; Speckle; Speckle noise; Superresolution; White light interferometry

Untreated ´blow-in´ fracture of the orbital floor causing a mucocele: report of an unusual late complication - Nkenke, Emeka; Häusler, Gerd; et al. (Journal of Cranio-Maxillofacial Surgery, 2005)
Background: Several severe complications have been described with blow-in fractures. Therefore, immediate surgical treatment of these fractures has been recommended. To date, there is only minimal knowledge on long-term complications of blow-in fractures that have remained untreated. The present case report describes a late complication of an untreated blow-in fracture of the orbital floor. Case: A 37-year-old male was involved in a car accident 16 years before. At that time, a non-dislocated midfacial fracture was diagnosed and remained untreated because of the lack of clinical symptoms. Four months before surgery an exophthalmos of the left globe began to develop. CT examination revealed a consolidated blow-in fracture of the left orbital floor and an opaque mass around the dislocated bony fragments. By an infraorbital approach the bony fragments and the surrounding mass were removed. Histological examination of the removed material revealed a cystic structure lined with respiratory epithelium. Therefore, the diagnosis 'post-traumatic mucocele in the orbit caused by dislocated respiratory epithelium from the maxillary sinus' was made. Conclusion: Even if blow-in fractures do not cause complications immediately after trauma, late complications like mucoceles can occur after several symptom-free years. Therefore, early reconstruction should be intended even in asymptomatic cases of blow-in fractures with minimal displacement of the bony fragments. © 2005 European Association for Cranio-Maxillofacial Surgery.
UnivIS-Import:2015-04-14:Pub.2005.nat.dphy.optik.1optik.untrea
Keywords: Alloplastic reconstruction of the orbital floor; Blow-in fracture; Exophthalmos; Mucocele; Untreated orbital floor fracture

Visualization and Detection of Small Defects on Car-Bodies - Häusler, Gerd; et al. (Proc. of Vision, Modeling and Visualization '99, 1999)
UnivIS-Import:2015-04-16:Pub.1999.nat.dphy.optik.1optik.visual

White-light interferometer with dispersion - an accurate fiber-optic sensor for the measurement of distance - Häusler, Gerd; et al. (Applied Optics, 2005)
We present a fiber-optical sensor for distance measurement of smooth and rough surfaces that is based on white-light interferometry; the sensor measures the distance from the sample surface to the sensor head. Because white light is used, the measurement is absolute. The measurement uncertainty depends not on the aperture of the optical system but only on the properties of the rough surface and is commonly ∼ 1 μm. The measurement range is approximately 1 mm. The sensor includes no mechanical moving parts; mechanical movement is replaced by the spectral decomposition of light at the interferometer output. The absence of mechanical moving parts enables a high measuring rate to be reached. © 2005 Optical Society of America.
UnivIS-Import:2015-03-09:Pub.2005.nat.dphy.optik.1optik.whitel